Convenient and Live Movement (CALM) for women undergoing breast cancer treatment: Challenges and recommendations for internet-based yoga research. (April 2018) - Addington, Elizabeth L.; Sohl, Stephanie J.; Tooze, Janet A.; Danhauer, Suzanne C.
Highlights: Women receiving breast cancer treatment were recruited for cancer-adapted yoga classes delivered by online videoconference. Qualitative data provide suggestions for overcoming technology- and cancer-related barriers to recruitment and retention. Results can inform the development of future trials of internet-delivered mind-body interventions for adults with cancer. Abstract: Objective: To conduct a pilot trial of internet-based, cancer-adapted yoga for women receiving breast cancer treatment. Design: Women undergoing radiation or chemotherapy for breast cancer were recruited for 12, 75-min, biweekly, cancer-adapted yoga classes delivered via internet-based, multipoint videoconferencing. Data were collected on feasibility and acceptability, including qualitative feedback from participants and the yoga instructor. Results: Among 42 women approached, 13 declined eligibility screening, and 23 were ineligible. All 6 women who were eligible provided consent, but 2 withdrew prior to beginning yoga classes. The remaining 4 participants attended 1–11 of 12 online yoga classes. In post-intervention interviews, participants and the instructor agreed that internet-based yoga classes hold great potential for increasing access and improving psychological outcomes in adults with cancer. Qualitative feedback from participants revealed suggestions for future trials of internet-based, cancer-adapted yoga classes, including: continued use of group format; offering more varied class times to accommodate patients' demanding schedules and fluctuating symptoms; enrolling patients after they have acclimated to or completed cancer treatment; streamlining the technology interface; and careful attention to participant burden when designing surveys/forms. The instructor recommended closed session courses, as opposed to rolling enrollment; teaching the same modified poses for all participants, rather than individual tailoring; and using a large screen to allow closer monitoring of students' class experience. Conclusions: Internet delivery may increase patients' access to cancer-adapted yoga classes, but cancer-related and technological barriers remain. This study informs how to optimally design yoga classes, technology, and research procedures to maximize feasibility and acceptability in future trials.